Boosting efficiency and stability for organic solar cells by subtle management electron-withdrawing terminal of electron acceptors based on asymmetric dual-donor centra. (February 2023) - Zhu, Jianing; Hao, Rulin; Wang, Junfeng; Sun, Dawei; Song, Xin; Zhu, Mengbing; Zhang, Bin; Liu, Yu; Tan, Hua; Zhu, Weiguo
Abstract: Non-fused-ring small-molecule acceptors (SMAs) have attracted great interest in organic solar cells (OSCs) due to their simple synthesis, plentiful structures and easily regulable morphology. However, the presented power conversion efficiencies (PCEs) are unsatisfactory for the OSCs with these SMAs. One of the main solutions is to develop high-performance simple SMAs and gain insights into their structure-property relationship. Here, we adopted an asymmetric dual-donor central subunit to design and synthesize two A-D-D′-A typed SMAs of IOEH-N2F and IOEH-4F with the same central subunit and different terminal, in which the D-D′ core consists of 2-ethylhexyloxy indenothiophene and dithienocyclopentadiene units. In comparison to the IOEH-4F with 5, 6-difluo-3-dicyanomethylidene indanon terminal, the IOEH-N2F with 6, 7-difluo-3-dicyano- methylidene cyclopenta [b]naphthalen-1-one terminal shows a larger planar framework with a higher crystallinity and an enhanced NIR absorption. Therefore, the IOEH-N2F binary OSCs exhibit higher PCE and device stability than the PM6 :IOEH-4F based OSCs. An appealing PCE of 14.25% is achieved in the optimal PM6 :IOEH-N2F bianry OSC, which has a 18% increase in comparison with that of the optimal PM6 :IOEH-4F binary one. More excitingly, this PCE still maintains original 86% in N2 atmosphere for 1000 h at room temperature. Our work indicates that photovoltaic properties and device stability of non-fused-ring SMAs can be improved by subtle management terminal of SMAs based on asymmetric dual-donor centra. Graphical abstract: Image 1 Highlights: Two simple SMAs are synthesized with the same asymmetric dual-donor centra and different acceptor terminal. The effect of donor centra and acceptor terminal on photoelectric properties and stability of SMAs is studied. PCE and device stability of SMA are improved by a subtle management of donor centra and acceptor terminal. The PM6:SMA based OSCs exhibit an advanced PCE of 14.25% by selecting acceptor terminal of SMA. The PM6:SMA based OSCs still maintains 86% level of the initial PCE for 1000 h in N2 atmosphere at room temperature.